It Can Be a “Very Fine Line”: Professional Footballers’ Perceptions of the Conceptual Divide Between Bullying and Banter - Newman, James A.; Warburton, Victoria E.; Russell, Kate (Frontiers in Psychology, 2022)
As a result of recent allegations of abuse and bullying in football, this study was focused on the welfare and safeguarding of English professional footballers. Given professional football normalizes forms of banter which might otherwise be seen as bullying in other contexts, the study sought to explore professional footballers’ perceptions of the dividing line between these two concepts. The study adopted a phenomenological approach, which focused on the essence of the participants’ perceptions and experiences. Guided by Interpretative Phenomenological Analysis (IPA) individual semi-structured interviews (MDuration = 44.10, SD =10.81 were conducted with 18 male professional footballers (Mage=19.83, SD=2.96) from three Premier League and Championship football clubs. The findings from this study revealed several key superordinate themes in relation to the dividing line between bullying and banter. These themes included 'perception', 'intentionality', 'detecting the line', and 'bantering'. The findings demonstrate how perceptions of bullying and banter are nuanced by individual differences among the players and the culture of the professional football context. Specifically, it was found that the professional football context can legitimize forms of humor blurring the lines between bullying and banter, challenging the typically positive view of the concept of banter in this environment. From an applied perspective, these findings highlight the need for coaches, players, and football clubs more broadly to address cultural expectations around banter in their environment, whilst educating individuals around their own perceptions of bullying and banter.